Antioxidant Activity and Bioactive Compound in a Functional Instant Drink Made from Mangosteen Peel and Rosella Extract - Yuarini, DewaAyu Anom (Media Ilmiah Teknologi Pangan (Scientific Journal of Food Technology); Vol 2 No 1 (2015))
The research aims to identify the effect of mangosteen peel and rosella formulation through antioxidant activity and bioactive compound contained in functional instant drink and to determine its highest formulation. The method utilized was complete random method that consists of 6 (six) stages. The variables observed were total of phenol, vitamin C, tannin and antioxidant. The data were analyzed using SPSS 17.0 version, and further analyzed with Duncan test. The research showed that the formulation was significantly effect on levels of phenol, tannin, ascorbic acid (Vitamin C), as well as on the capacity of antioxidant. The higher level of phenol and tannin cause the higher antioxidant capacity in functional instant drinks. The functional instant drink with the highest antioxidant capacity was  made of mangosteen peel, rosella flower and water formulation, with a ratio of 4:1:50.
Keywords: Bioactive compound, antioxidant activity, functional instant drink, mangosteen peel, rosella flower